Maths

posted by .

Express the sum using summation notation:

1 - 1/2 + 1/3 - 1/4 + 1/5 - ... (to 3n terms)

If I'm doing this right so far, with k=1 (the number on bottom of the sigma), the equation after the sigma would be

((-1)^(k+1)) / k

I'd be able to figure out the term on top of the sigma, n, if I knew the value, but I don't understand how to get it because of the way it is worded. Please help, and correct me if what i've done so far is wrong.

  • Maths -

    they did not tell you what n is so you can say 3n

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. further mathematics

    The roots of the eqn, x^4 + px^3 + qx^2 + rx + s = 0 where p, q, r, s are constants and s does not equal to 0, are a, b, c, d. (i) a^2 + b^2 + c^2 + d^2 = p^2 -2q (in terms of p & q) (ii) 1/a + 1/b + 1/c + 1/d = -r/s (in terms of r …
  2. math

    Hi. I'm having trouble with the summation of n from i=2 of ((2^n-i)(2^n)). Any help would be greatly appreciated! the way I am reading the question you have i is going from 2 to n so there will be n-1 terms using i = 2,3,4,..,n I get …
  3. Maths

    Express the sum using summation notation: 1 - 1/2 + 1/3 - 1/4 + 1/5 - ... (to 3n terms) If I'm doing this right so far, with k=1 (the number on bottom of the sigma), the equation after the sigma would be ((-1)^(k+1)) / k I'd be able …
  4. Maths

    Express the sum using summation notation: 1 - 1/2 + 1/3 - 1/4 + 1/5 - ... (to 3n terms) If I'm doing this right so far, with k=1 (the number on bottom of the sigma), the equation after the sigma would be ((-1)^(k+1)) / k I'd be able …
  5. Algebra

    Express the sum below using summation notation. Use 1 as the lower limits of summation and i for the index of summation. 1/3+2/4+3/5+...+18/20
  6. Pre-CalcPlease check

    Please check: 1.Write in expanded form: this is a sigma notation- 4 on top signma in middle k=1 on bottom to right of sigma is (k-1)(k-2) I solved: k=1 (1-1)(1-2)=0(-1)=0 K=2 (2-1)(2-2) = 1(0)=0 k=3(3-1)(3-2)=2(1)=2 k=4 (4-1)(4-)=3(2)=6 …
  7. Calculus need help badllyyy!

    Use the expressions for left and right sums and the table below. right-hand sum = summation (n above and i =1 on the bottom) f(ti) * change in t = f(t1) * change in t + f(t2) * change in t + .... + f (tn) * change in t left-hand sum …
  8. Math help quickly

    Use the expressions for left and right sums and the table below. right-hand sum = summation (n above and i =1 on the bottom) f(ti) * change in t = f(t1) * change in t + f(t2) * change in t + .... + f (tn) * change in t left-hand sum …
  9. MATH

    Expand f(x)=ln (1+x/1-x) in a Taylor Series about x=0. You must express your answer using summation notation. ---This is what I tried to do--- So I was thinking of taking the derivative of ln(1+x/1-x) and get 2/x^2-1 And then use the …
  10. Algebra 2

    Q: What represents the sum of a geometric series with 8 terms whose first term is 3 and common ratio is 4. A: 65,535 Is my answer right?

More Similar Questions